2019
DOI: 10.1111/ijd.14553
|View full text |Cite
|
Sign up to set email alerts
|

Modified basic and specific (BASP) classification for pattern hair loss

Abstract: Background In 2007, Lee et al. introduced a basic and specific (BASP) classification for pattern hair loss that was comprehensive and applicable regardless of race or gender. However, this BASP classification has several limitations. Frontal type hair loss classification is relatively crude, and a specific hair loss pattern cannot be ascertained when hair loss is associated with the temporal and occipital areas. Methods In our modified BASP classification, frontal type classification was subdivided into five i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…6 However, the original definition of HDD ≥20% was not explicitly detailed, leading to an interpretation in subsequent studies that it involved cases where more than 20% of hairs are less than 40 μm in diameter. 2 , 4 , 20 Our in-depth evaluation at a fixed 20% HDD cutoff revealed that a 45-μm threshold offers superior diagnostic performance for the Korean population, marked by the highest Youden index. This is particularly relevant considering that Korean individuals typically have thicker hair compared to those of Caucasian ethnicity.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…6 However, the original definition of HDD ≥20% was not explicitly detailed, leading to an interpretation in subsequent studies that it involved cases where more than 20% of hairs are less than 40 μm in diameter. 2 , 4 , 20 Our in-depth evaluation at a fixed 20% HDD cutoff revealed that a 45-μm threshold offers superior diagnostic performance for the Korean population, marked by the highest Youden index. This is particularly relevant considering that Korean individuals typically have thicker hair compared to those of Caucasian ethnicity.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, using a specific hair diameter threshold may not account for individual variations in hair thickness, highlighting the need for a more personalized diagnostic approach. Diagnostic assessments for AGA often rely on established clinical scales like the Norwood-Hamilton, Ludwig, and BASP classifications, 2 , 6 , 22 which, despite their ease of use and intuitive nature, are limited by their subjective quantification of the condition. 19 Future research should explore the correlation between physicians' perceptions of HDD and its quantitative measurements to address these subjective aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The new BASP classification will not only facilitates in the development of a unified and simplified algorithm, but also help formulates treatment guideline. [19][20]…”
Section: Introductionmentioning
confidence: 99%